The Existential Relevance of Art for Human Life (Itinera, 2021)
What is the relevance of art for human life? This question can be answered if life is understood from life-performance and art from artworks. From this perspective, the human being – understood as a being in a self-researching process – and the work of art – conceived as an experience-figure – show a structural correspondence: a constitutive unfathomability. Both, human being and art, can only be adequately understood as open processes of their respective self- realization. Because of this correlation and, at the same time, considering their fundamental difference, the aesthetic experience enables the human being to objectify the process of self-research. Thus, the existential relevance of art to life becomes concrete in that the aesthetic experience that makes the artwork the unique unfathomability that it is, reveals itself as an excellent path to the process of self-research, which makes human beings the unique unfathomability that he or she is.
Keywords: artwork, self-realization-process, experience-figure, unfathomability.